2020
DOI: 10.1016/j.celrep.2020.107640
|View full text |Cite
|
Sign up to set email alerts
|

SAMHD1 Limits the Efficacy of Forodesine in Leukemia by Protecting Cells against the Cytotoxicity of dGTP

Abstract: Highlights d SAMHD1-deficient cells die upon exposure to deoxyguanosine (dG) d dG induces apoptosis in cells, including cancer cells, lacking SAMHD1 d PNP-inhibitors such as forodesine and dG synergistically trigger cell death d dG and forodesine kill mutated leukemic cells without SAMHD1 expression

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…The observation that AML, T-PLL and MCL with altered SAMHD1 expression (either by deletion, mutation or other mechanisms) respond differently might therefore be explained by differences in cell type and by different functional effect depending on type of alteration. A recent article by Davenne and co-workers[15] reported functional and pharmacological effects of SAMHD1 depletion in CLL cells, notably identifying forodesine as a potent agent in cells lacking SAMHD1 and elucidating the underlying mechanism. These results raise the possibility of a targeted use of forodesine in MCL carrying disrupting SAMHD1 mutations, further highlighting the potential of SAMHD1 as a predictive biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that AML, T-PLL and MCL with altered SAMHD1 expression (either by deletion, mutation or other mechanisms) respond differently might therefore be explained by differences in cell type and by different functional effect depending on type of alteration. A recent article by Davenne and co-workers[15] reported functional and pharmacological effects of SAMHD1 depletion in CLL cells, notably identifying forodesine as a potent agent in cells lacking SAMHD1 and elucidating the underlying mechanism. These results raise the possibility of a targeted use of forodesine in MCL carrying disrupting SAMHD1 mutations, further highlighting the potential of SAMHD1 as a predictive biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Using cell viability analysis and mass cytometry, we found that leukemic cells from patients with SAMHD1 loss-of-function mutations were killed by forodesine and dG (Figure 1). 2 In contrast, normal PBMCs and leukemic cells with SAMHD1 survived.…”
Section: Main Textmentioning
confidence: 98%
“…However, our studies led to a very different observation: cells without SAMHD1 started dying after feeding with dNs, whereas cells with SAMHD1 were unaffected. 2 Amongst the four dNs, deoxyguanosine (dG) showed the highest toxicity. dG was converted intracellularly to deoxyguanosine triphosphate (dGTP) and triggered apoptosis in a variety of SAMHD1-deficient cell types and cell lines from human and mouse, but not in SAMHD1-sufficient cells.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations